Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI): Dampak Terhadap Hasil Belajar Fisika Siswa - Ariani, Tri (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2017)
The research aims to know the influence of students studying physics by using cooperative learning model Team Assisted Individualization (TAI) type in learning physics on class X SMAN 8 Lubuklinggau the Academic Year 2016/2017. This type of research is experimental research, the research design used in the form of pre-test and post-test control group design. Data collection techniques in this research are essay test in the form of as much as seven items. The essay is to determine students’ learning outcomes in the cognitive domain. The samples were taken from class X.1 and class X.2. The average value of the experimental class in initial tests was at 40.64 and 83.41 for the final test. While the average value of the initial test in control class was at 32.16 and for the final test at 75.73. With t = 2.604 df = 48 and α = 0.05, ttable value is 1.684. So tcount> ttable, then accept and reject H0 Ha. Based on this analysis we can conclude the results of the experimental class which is learning using cooperative learning model Assisted Individualization Team (TAI) type is higher than the average value of the control class that using conventional cooperative learning.Penelitian ini bertujuan untuk mengetahui pengaruh hasil belajar fisika siswa pada ranah kognitif dengan menggunakan model pembelajaran kooperatif tipe Team Assisted Individualization (TAI) siswa kelas X SMA Negeri 8 Lubuklinggau Tahun Pelajaran 2016/2017. Jenis penelitian ini adalah penelitian eksperimen, dengan desain penelitian berbentuk pre-test dan post-test kontrol group design. Teknik pengumpulan data dalam penelitian ini adalah tes berbentuk soal essay sebanyak 7 butir soal. Kelas sampel diambil kelas X.1 dan kelas X.2. Nilai rata-rata kelas eksperimen pada tes awal sebesar 40,64 dan tes akhir sebesar 83,41. Sedangkan nilai rata-rata kelas kontrol pada tes awal sebesar 32,16 dan pada tes akhir sebesar 75,73. Dengan thitung = 2,604 dk = 48 dan α = 0,05, maka nilai ttabel adalah 1,684. Jadi thitung> ttabel, maka terima Ha dan tolak H0. Berdasarkan analisis tersebut dapat disimpulkan ada pengaruh model pembelajaran kooperatif tipe Team Asissted Individualization (TAI) terhadap hasil belajar fisika siswa.